Manajemen Tenaga Pendidik dan Kependidikan di Sekolah Dasar - Tauba, Zahrah Rahmadina; Mukhlishoh, Salwa Karimah; Rosmaldi, Rezka Rachima; Pertiwi, Santhi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article discusses the importance of educators and educational management in supporting the quality of education in Elementary Schools. Through the method of literature study, talent management in educational settings, especially Islamic-based research, can have a significant impact on the quality of learning and the formation of student personality. The management process includes planning, procurement, development, promotion, termination, compensation, and appreciation. The results of several schools, such as the excellent CT Foundation of Middle School, SMAN 3 Medan, SMAN 1 Perbaungan, and SMAN 2 Lubuk Pakam, show that the quality of educators is highly correlated with the use of good management systems, especially those related to the appropriateness in the field of education and the integrity of learning tools. In addition, character education can be achieved optimally only when educators act as examples. This study highlights the importance of the synergistic effect between technical management and character values to support a sustainable national education system.